Utilization of Eugenia Caryophyllata Thumb, Piper Nigrum Linn, and Thymus Vulgaris L Extracts on the Fungal-Invaded Limestone of some Monumental Buildings in Cairo, Egypt - Azab, Amira Saad; Ali, Gomaa A. M.; Mohd Azmuddin, Abdullah; Algarni, H.; K. F., Chong (PSP and PRT, 2018)
The present work reports on the use of some medicinal plants as candidates against fungal contamination in historical buildings. Isolation of different fungal species was made from three different buildings in old Cairo (mosque of Tameem Al-Rassafy, madrasa of Azbak Al-Yusufi, and mosque of Yusuf Agha Al-Heen), which had undergone deterioration on their limestone surfaces. The plants were collected from the Egyptian herbalism and duly confirmed and identified as that belonging to Eugenia caryophyllata (Clove), Piper nigrum, and Thymus vulgaris. Extraction of the crude oil was carried out using steam distillation method and the antifungal activities of the crude oil extracts were examined on the isolated fungi. The potential sterilization of the crude oil extracts was further investigated on the limestone samples and the effectiveness of the treatment evaluated with laboratory tests. The results indicated that the formulated treatment was suitable for monumental stone conservation.